The Role of Technology in English Classroom: Exploring Teacher's and Students' perspectives at School of Pontianak - Laura, Lidya; Maliqul Hafis; Dian Shinta Sari; Desi Sri Astuti; Purwiyanti (Journal of English Language Teaching and Education (JELTE), 2025)
This study aims to explore the role of technology in English language learning at SMP Negeri 13 Pontianak from the perspectives of teachers and students. A descriptive qualitative approach was employed, utilizing observation, semistructured interviews, and documentation as data collection techniques. The research instruments included an observation sheet to record the use of technology in the classroom, interview guidelines to explore the perceptions and experiences of teachers and students, and a documentation checklist to gather relevant teaching materials and media. The participants consisted of one English teacher and five eighth-grade students selected through purposive sampling. The data collected were analyzed using Braun and Clarke’s thematic analysis, which involves six steps: familiarizing with data, generating initial codes, searching for themes, reviewing themes, defining and naming themes, and producing the final report. The findings revealed that technology such as Kahoot, projectors, and mobile devices effectively enhanced students’ motivation, engagement, and understanding of the learning material. Both the teacher and students expressed positive attitudes toward technology integration in the classroom. However, several challenges were identified, including limited school infrastructure,  unstable internet connectivity, and varying levels of digital literacy among students. This study recommends continuous teacher training and improvements in school facilities to optimize technology-based learning. Keywords: Learning technology, teacher and student perceptions, technology integration